The Adaptation of Intentional Immigrant Entrepreneurs: A Case Study - Prue Cruickshank; Ann Dupuis (Entrepreneurial Business and Economics Review, 2015)
Objective: This paper describes the experiences of a group of intentional immigrant entrepreneurs (IIEs) who have successfully set up a business within three years of arrival in a new country. It shows how various forms of symbolic capital are successfully deployed at each stage of the entrepreneurial process and asserts that the study of intentional, well-resourced immigrants, can contribute to understanding immigrant entrepreneurs adaptation to their new settings and also inform immigration policy. Research Design & Methods: Qualitative in-depth interviews were conducted with a sample of New Zealand intentional immigrant entrepreneurs. The iterative analytical process used revealed the various dimensions of symbolic capital necessary for adaptation to the host country and to fulfilling visa requirements to gain residency. Findings: This paper demonstrates that the successful adaptation of IIEs, while in the first instance requiring adequate financial capital, also requires the strategic use of human, cultural and social capital, in different ways and at different times in the entrepreneurial process, to overcome the obstacles and barriers to success. Implications & Recommendations: As immigration policy makers seek to balance global migrant pressures and international obligations against internal national economic and political demands, the results of this study could resonate with both global policy analysts and scholars engaged in immigrant entrepreneurship. Contribution & Value Added: This article adds to the relatively small body of scholarship on IIEship, particularly those who, unlike the majority of immigrant entrepreneurs, do not establish a business within ethnic communities.